Psychophysiologic symptom relief therapy for chronic back pain: hypothesis and trial rationale - Paschali, Myrella; Thompson, Garrett S.; Mehta, Shivani; Howard, Patricia M.; Yamin, Jolin B.; Edwards, Robert R.; Donnino, Michael W. (Frontiers in Pain Research, 2024)
Chronic pain syndromes affect over one-third of the US adult population and often lead to significant disability and a reduced quality of life. Despite their high prevalence, causal links between chronic pain syndromes and anatomic abnormalities are often not apparent. Most current chronic pain treatments provide modest, if any, relief. Thus, there is a pressing need to understand the causal mechanisms implicated in chronic pain as a means to develop more targeted interventions for improvement in clinical outcomes and reduction in morbidity and financial burden. In the present manuscript, we summarize the current literature on treatment for chronic pain, and hypothesize that non-specific chronic back pain (without a clear organic etiology, such as tumors, infections or fractures) is of psychophysiologic origin. Based on this hypothesis, we developed Psychophysiologic Symptom Relief Therapy (PSRT), a novel pain reduction intervention for understanding and treating chronic pain. In this manuscript, we provide the rationale for PSRT, which we have tested in a pilot trial with a subsequent larger randomized trial underway. In the proposed trial, we will evaluate whether non-specific chronic back pain can be treated by addressing the underlying stressors and psychological underpinnings without specific physical interventions.